Tourist Motivation to Visit Bumi Langit as a Permaculture Gastronomic Tourist Attraction in Mangunan Bantul, Yogyakarta - Muntaha, Baitul Ma'mur; Kuswardani, Rina; Sulasmi, Sri (Journal of Tourism Education, 2023)
Abstract: Bumi Langit is a gastronomic tourism object that applies the concept of permaculture. Permacutur is a concept of integrated and organic agriculture that applies the principle of balance in a sustainable and sustainable way of life. This study aims to apply the concept of miss helix as a component of gastronomic tourism at the Bumi Langit stall as a permaculture gastronomic tourist attraction.The research method used is a qualitative method, while data collection techniques are carried out by interviews, observations, literature studies and documentation studies. From this research, it is expected to be able to arouse the motivation of tourists to return to Warung Bumi Langit because this object is the only tourist attraction that applies the principles of permaculture in Yogyakarta.